Gestión de riesgo crediticio y nivel de morosidad en la COOPAC RONDESA – agencia Huamachuco 2020 - Altamirano Rosado, Araceli Julisa (2022)
For the development of this research, it was carried out with Cooperativa Rondesa - Agencia Huamachuco as the study entity, which develops its activities in the district of Huamachuco and surrounding geographical areas, with the main objective of determining how the Management of Credit risk with the level of delinquency of the COOPAC Rondesa, the research carried out according to its scope is descriptive, non-experimental and correlational, the Inductive-Deductive Method, Hypothetical-Deductive Method was used, data collection and the survey as a research technique, for the reliability of the data, the Cronbach's Alpha method was applied, obtaining 0.859 for the data collection instrument of both variables, and for the variable Credit risk management an alpha equal to 0.839, in the variable Delinquency level an alpha equal to 0.884 was determined; for this research we worked with two populations, for the first variable they were the collaborators of the Cooperative, made up of 19 and we did not work with a sample, and the second population were the partners made up of 850, the sample was 128 partners, to said The data collection instrument was applied to the samples, and with the data obtained it was possible to meet the objectives of the thesis, verify the research hypothesis through the Spearman correlation coefficient, and obtain as the main conclusion that, the Management of Credit Risk is positively related to the Delinquency Level of COOPAC Rondesa - Agencia Huamachuco 2020